Thermoelastic Phase Transformations and Microstructural Characterization of Shape Memory Alloys - Adiguzel, O. (Springer, 2018)
Shape memory effect is a peculiar property exhibited a certain alloy systems with special chemical compositions in the beta-phase fields of alloys and other materials like polymers. Successive martensitic transformations, thermal induced and stress induced martensitic transformations, govern shape memory effect in shape memory alloys. Martensitic transformations are structural phase transformations, and thermal induced martensitic transformation occurs as martensite variants with lattice twinning in crystallographic or atomic scale in materials on cooling below martensite finish temperature. Twinned martensite structures turn into detwinned martensite structure by means of stress induced transformation by deforming plastically in a strain limit in martensitic condition. Shape memory alloys are in the fully martensitic state below martensite finish temperature with fully twinned structure and can be easily deformed through variant reorientation/detwinning process. Thermal induced martensitic transformation is lattice-distorting phase transformation and occurs as martensite variants with the cooperative movement of atoms by means of shear-like mechanism. Martensitic transformations occur by two or more lattice invariant shears on a {110}-type plane of austenite matrix, as a first step, and the transformed region consists of parallel bands containing alternately two different variants. Copper based alloys exhibit this property in metastable beta-phase region, which has bcc-based structures at high temperature parent phase field. Lattice invariant shears are not uniform in these alloys, and the ordered parent phase structures martensitically undergo the complex layered structures.
NATO Advanced Research Workshop on Nanostructured Materials for the Detection of CBRN -- AUG 14-17, 2017 -- Kiev, UKRAINE
Keywords: Thermoelastic phase transformations; Shape memory effect; Twinned and detwinned martensites